Postoperative Resource Utilization and Survival among Liver Transplant Recipients with Model for End-Stage Liver Disease Score ≥40: A Retrospective Cohort Study - Filipe S Cardoso; Constantine J Karvellas; Norman M Kneteman; Glenda Meeberg; Pedro Fidalgo; Sean M Bagshaw (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Cirrhotic patients with Model for End-stage Liver Disease (MELD) score ≥40 have high risk for death without liver transplant (LT).